Evaluation of laser-printed paper deinking quality facilitate by lipase and esterase enzymes / NurulShafika Azmi and Nik Raikhan Nik Him - NurulShafika, Azmi; Nik Raikhan, Nik Him (2015)
The paper industry is one of the most developed, yet the most polluter industry. Recycling program is developed as one of the steps to counter with this environmental issue. The key of recycling process is the successfulness of the deinking process. Considering the concern to the environmental problem caused by the conventional deinking process, enzymes are applied. Enzymatic bio-deinking are proven to reduce the use of harmful chemicals and production of enormous wastewater. Research had been conducted to compare the deinkability and the quality of the secondary paper produced from enzymatic deinking and virgin pulp paper. The degree of ink removal is measured by the optical parameter improvements. Results indicate that enzymes facilitate ink removal successfully and the brightness increases very significantly among experimental trials. Lipase and esterase enzymes are applied in their optimum condition to facilitate deinking of laser-printed paper. The method applied is using GE brightness technique that commonly applied in United State. The methods also describe by TAPPI standards T 452. Lipase and esterase are applied individually and undergo concoction by a ratio of 100:100 and 100:50. The result indicates that brightness is varied. Individual lipase produced 48.48% paper brightness, whereby esterase is 39.47% compared to control. Concoction is done to optimize the result and the best result achieved is 71.62%, by concoction of lipase and esterase with ratio 100:100. The effect of the enzymes and enzymes concoctions on fiber morphological changes during the deinking process was studied by scanning electron microscopy (SEM).